Hubungan Self-Effecacy dan Keterampilan Komunikasi dengan Kecemasan Berbicara di Depan Umum - Wahyuni, Endang (Jurnal Komunikasi Islam, 2015)
The research aims to know the relationship among self-efficacy and communication skills toward public spea–king anxiety. The subject of the research is 50 students in the 6th semester at Faculty of Dakwah and Communication, UIN Sunan Ampel Surabaya. Using multiple regression analysis and partial correlation, the study reveals that t. The result shows that the self-efficacy and communication skills are correlated with public speaking anxiety. High skill of communication cannot reduce public speaking anxiety. The hypothesis that says there is a negative relationship between communication skills and public speaking anxiety, not proven. It means that the hypothesis is rejected. The research results reveal that perhaps there are other factors influence the anxiety of student’s public speaking skills.